In-situ Measurement of Pedestrian Outdoor Thermal Comfort in Universities Campus of Malaysia - Elmira Othman, Nurnida; Ahmad Zaki, Sheikh; Huda Ahmad, Nurul; Razak, Azli (KnE Social Sciences, 2019)
The present study is intended to evaluate an outdoor thermal comfort at two universities campus in Malaysia. Field measurement and questionnaire survey were conducted simultaneously to assess the microclimatic condition and pedestrian thermal sensation. A total of 3033 samples were collected at seven different sky view factor (SVF) values that range from 0.2 to 0.9. The physiological equivalent temperature (PET) was estimated to evaluate outdoor thermal comfort. It was observed that at a highly shaded area (SVF < 0.35) the respondent’s thermal sensation vote (TSV) are neutral (> 25%), acceptable for thermal acceptance vote (TAV) (> 50%) and no change (> 50%) for thermal preference vote (TPV). For moderate shaded (0.35 ≤ SVF ≤ 0.70) TSV was voted as hot (> 25%), acceptable for TAV (40%), and prefer slightly cooler for TPV (>50%). For less shaded area (0.70 < SVF ≤ 1), TSV was voted as hot and very hot (> 25%), acceptable for TAV (>40%) and prefer slightly cooler for TPV (> 40%). Moreover, the PET value increases simultaneously with the increase of SVF. Results thus suggest that at any given activities such as sitting, walking, and standing also caused effects slightly on the way people thermally perceive it during the on-campus daytime.